Revision of the Neotropical species of the caddisfly genus Wormaldia McLachlan (Trichoptera: Philopotamidae) - Muñoz-Quesada, Fernando J.; Holzenthal, Ralph W. (Zootaxa, 2015)
Wormaldia McLachlan 1865 is the 2nd largest genus in the family Philopotamidae (Trichoptera) after Chimarra Stephens 1829 and is diverse and widely distributed, with ca. 175 extant species in all biogeographic regions except the Australasian. In this monograph, 14 previously described species are recognized for the Neotropical region: W. alicia Bueno-Soria, Santiago-Fragoso, & Barba-Alvarez 2005 [Mexico]; W. arizonensis (Ling 1938) [Mexico, USA]; W. cornuta Bueno-Soria & Holzenthal1986 [Mexico]; W. dampfi Ross & King 1956 [Mexico, Nicaragua]; W. dorsata Ross & King 1956 [Mexico]; W. endonima Ross & King 1956 [Mexico]; W. esperonis Ross & King 1956 [Mexico]; W. insignis (Martynov 1912) [Peru]; W. luma Bueno-Soria & Holzenthal 1986 [Mexico]; W. matagalpa Flint 1995 [Costa Rica, Guatemala, Nicaragua]; W. palma Flint 1991 [Colombia]; W. planae Ross & King 1956 [southwestern USA, Mexico, Caribbean, Central America, and northern South America]; W. prolixa Flint 1991[Colombia]; and W. tarasca Bueno-Soria & Holzenthal 1986 [Mexico]. Also, 36 additional Neotropical species are newly diagnosed, described, and illustrated: W. andrea [Ecuador]; W. anhelitus [Central America]; W. araujoi [Ecuador]; W. aymara [Bolivia]; W. barbai [Mexico]; W. bolivari [Venezuela]; W. boteroi [Colombia]; W. buenorum [Mexico]; W. calderonae [Mexico]; W. chrismark [Panama]; W. contrerasi [Panama]; W. dachiardiorum [Colombia]; W. eberhardi [Panama]; W. flinti [Bolivia, Panama]; W. francovilla [Panama]; W. fredycarol [Costa Rica, Panama]; W. gallardoi [Costa Rica, Panama]; W. gonzalezae [Venezuela]; W. hedamafera [Costa Rica, Nicaragua]; W. imberti [Costa Rica]; W. inca [Peru]; W. isela [Mexico]; W. juarox [Costa Rica]; W. lauglo [Panama]; W. machadorum [Costa Rica, Panama]; W. maesi [Nicaragua]; W. menchuae [Guatemala]; W. monsonorum [Costa Rica]; W. navarroae [Mexico]; W. paprockevi [Costa Rica]; W. saboriorum [Panama]; W. tocajoma [Costa Rica]; W. trondi [Costa Rica, Panama]; W. tupacamara [Bolivia]; W. zunigae [Colombia]; and W. zunigarceorum [Costa Rica, Panama]. In addition, the species W. arcopa Denning 1966 from Panama is considered a junior subjective synonym of W. planae. Furthermore, new distribution records for the Neotropical region for several species are given. Diagnoses, redescriptions, and illustrations of the male genitalia of the other 14 described Neotropical species in the genus are also presented. Illustrations of the forewing and hind wing of 19 species are also given. A structural terminology for male tergum X is proposed. Finally, a key for identification of males of all Neotropical species is provided.